Effect of non-stationary current regimes on the morphology of silver electrodeposits - Aleksandar T. Dimitrov, Perica Paunović, Orce Popovski, Dragan Slavkov, Željko Kamberović and Svetomir Hadži Jordanov (Serbian Chemical Society, 2009)
This work is concerned with the use of reverse current regimes in order to form small-grained and compact silver deposits during the electrorefining process. Several parameters were varied, i.e., i) anodic overpotential, ii) cathodic vs. anodic time ratio and iii) duration of the anodic pulse. After optimization of these parameters, phosphate ions were added and the electrolyte was stirred. The effects of a rise of the anodic overpotential on the grain sizes of the silver deposit and compactness were studied. Prolongation of the anodic time had a similar influence but with a decrease in current efficiency. An increase of the cathodic vs. anodic time ratio caused an enlargement of the grains and a decrease in the compactness of the deposit. Optimal morphological characteristics were obtained when PO4(3-) were added and the electrolyte was stirred.